Mongolia : Gender Disparities in Labor Markets and Policy Suggestions - Khan, Tehmina; Aslam, Monazza (World Bank, Washington, DC, 2014)
Mongolia has made strong progress on key gender-related Millennium Development Goals (MDGs) in recent years. Gender indicators in education and health are also better in many respects than in comparator countries in the East Asia and Pacific region. Women have a limited presence in higher level managerial positions and in entrepreneurial work, and working women also have to shoulder most of the household and care duties compared to men. These inequalities can have large impacts on development, growth and productivity as well as pervasive intergenerational social costs. Removing impediments to full and equal participation for women in the economy, providing equal access to economic resources and opportunities and eliminating discrimination can boost productivity and competitiveness for firms with wider benefits for the economy and within the household. A range of potential policy actions can be considered, including improving employment outcomes (wages, career progression) for women in the public sector, introducing more friendly parental leave policies that cover both fathers and mothers, improving child care services and introducing affirmative action policies in sectors where women are acutely under-represented such as mining. In addition, business regulations can be streamlined to make it easier to start and operate businesses for both men and women. Other policies that may be helpful include promoting awareness of and encouraging the development of (appropriately regulated and supervised) micro-lending institutions.